Mini Bone Block Distraction Subtalar Arthrodesis (SAMBB) in the Management of Acquired Adult Flatfoot with Subtalar Arthritis: A Modification to the Grice–Green Procedure - Mosca, Massimiliano; Caravelli, Silvio; Vannini, Francesca; Pungetti, Camilla; Catanese, Giuseppe; Massimi, Simone; Fuiano, Mario; Faldini, Cesare; Giannini, Sandro (Joints, 2019)
Adult acquired flatfoot encompasses a wide range of deformities. The goal of surgical treatment of adult acquired flatfoot is to achieve proper alignment of the hindfoot and maintain as much flexibility as possible in the foot and ankle complex; nevertheless, if subtalar arthritis is present, subtalar arthrodesis is usually mandatory. A lateral approach over the sinus tarsi is performed and subtalar joint is prepared removing remaining cartilage, reduced up to 5 degrees of heel valgus, and stabilized with a Kirschner wire. The site of insertion of the corticocancellous bone graft, harvested from the ipsilateral proximal tibia, is prepared carving a vertical groove into the talar and calcaneal edges. Additional autologous cancellous chips, harvested from the proximal tibia, can be positioned and pressed with a beater into the sinus tarsi to enhance fusion. The technique described is a modification of the extra-articular arthrodesis originally proposed by Grice. mini bone block distraction subtalar arthrodesis is a simple and effective technique which permits a subtalar fusion with a restored orientation of the hindfoot and ankle alignment in acquired flatfoot with subtalar arthritis.
Keywords: flatfoot; valgus deformity; subtalar; arthrodesis; bone graft